Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I've been using the following theorem in my intro ODE course:

If $F(s) = \mathscr{L}\left\{ f(t) \right\}$ and $n\in\mathbb{N}$, then $\mathscr{L}\left\{t^n f(t) \right\} = (-1)^n\frac{d^n}{ds^n}F(s).$

What is the inverse of this transform? For instance, say I wanted to take $$ \mathscr{L}^{-1}\left\{ \frac{s}{(s^2+16)^2} \right\}.$$ I can see that the result would be $\frac{1}{8}t\sin(4t)$. But, how would one go about manually working this out (and particularly in general)?

share|improve this question

2 Answers 2

up vote 2 down vote accepted

ILTs like this may be evaluated using the residue theorem: the ILT is, in the this case, the sum of the residues at the poles to the left of the vertical line of integration. Here, the poles at $s_{\pm}=\pm 4 i$ are double poles.

The residue of a double pole $s=s_0$ of a function of the form

$$f(s) = \frac{p(s)}{q(s)^2}$$

is given by the expression

$$\text{Res}_{s=s_0} \frac{p(s)}{q(s)^2} = \frac{p'(s_0)}{q'(s_0)^2} - \frac{q''(s_0) p(s_0)}{q'(s_0)^3}$$

In this case, $p(s)=s e^{s t}$ and $q(s)=s^2+16$. Using the above ingredients, it is not hard to show that the ILT is

$$\begin{align}\frac{1}{i 2 \pi} \int_{c-i \infty}^{c+i \infty} ds \frac{s}{(s^2+16)^2} e^{s t}\\ &= \left [\frac{1+i 4 t}{-64} - \frac{8 i}{-512 i} \right ] e^{i 4 t} + \left [\frac{1-i 4 t}{-64} - \frac{-8 i}{512 i} \right ] e^{i 4 t} \\ &= \frac18 t \, \sin{4 t}\end{align}$$

share|improve this answer

Observe that $$\int \frac s{(s^2+16)^2}ds=-\frac1{s^2+16}+C\iff \frac{d \left(\frac1{s^2+16}\right)}{ds} =- \frac s{(s^2+16)^2}$$

and from this, $$\mathscr{L}^{-1}\left\{ \frac1{(s^2+16)} \right\}=\frac{\sin4t}4$$

So, $$\mathscr{L} \left\{ t^1\cdot\frac{ \sin 4t}4 \right\}=(-1)^1\frac{d^1}{ds^1}\left(\frac1{s^2+16}\right)=+\frac{2s}{(s^2+16)^2} $$

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.